The Tudeh Party of Iran and the peasant question, 1941–53. Issue 6 (1st November 2020) - Randjbar-Daemi, Siavush
Abstract: This article will examine the Tudeh Party of Iran's (TPI) attitude and agency towards the peasant question between its foundation in 1941 and the end of the party's ability to operate in the domestic political scene in 1953. Based on a close reading of party printed material and other relevant primary sources from those dozen years, the study will analyse the TPI's attempt to formulate a coherent and practicable stance on the pressing issue of the amelioration of the peasant condition during the early stages of its formation and develop a lasting presence, with varying degrees of success, within the large peasant contingent of the Iranian population of the time until the August 1953 coup d'état which brought an end to the activities of the party's front organisations, including the body devoted to the peasant question. Besides focusing on the formations through which the Tudeh sought to engage directly with rural communities and formulate a platform based on their grievances and requests, this article will also compare the Tudeh's agency within this segment of the Iranian population with its efforts across other strata of the Iranian society at the time as well as the party's reactions to peasant-oriented initiatives carried out by both local and national administrations during this period.